ANALYSIS OF FINANCIAL DISTRESS ON INFRASTRUCTURE COMPANIES LISTED AT INDONESIA STOCK EXCHANGE USING S-SCORE MODEL - Hutabarat, Francis M.; Manurung, Christine Surya (Prosiding Seminar Nasional INDOCOMPAC)
Abstract: It is important for a company to be able to predict the probability of its financial distress. Moreover, a company need to assessed the losses that would occur under various level of financial distress. The poor performance of a firm is caused by the financial distress itself. The ability of a company to be able to compete is determined by the performance of the company itself. Companies that are not able to compete to maintain its performance will gradually displaced from the environmental industry and will be bankrupt. In order for the survival of a company is maintained, then the management should be able to contain or even more spur increased performance. The method in this study is descriptive, and Springate method of S-Score were used to analyzed the data given from companies listed in the Infrastructure, Utilities and Transportaton Sector at Indonesia Stock Exchange. Results from the study showed that in the calculation using Springate method there two comapanies in the bankrupt categories namely META and JSMR in year 2014 whereas one company is completely solvent, they are CMNP based on year analysis period of 2010-2014. Keywords: Springate Method, Bankruptcy, Indonesian Stock Exchange